The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/cbic.201900282
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lipid Saturation, Hydrophobic Length and Cholesterol on Double‐Arginine‐Containing Helical Peptides in Bilayer Membranes

Abstract: Membrane proteins are essential for many cell processes yet are more difficult to investigate than soluble proteins. Charged residues often contribute significantly to membrane protein function. Model peptides such as GWALP23 (acetyl‐GGALW5LAL8LALALAL16ALW19LAGA‐amide) can be used to characterize the influence of specific residues on transmembrane protein domains. We have substituted R8 and R16 in GWALP23 in place of L8 and L16, equidistant from the peptide center, and incorporated specific 2H‐labeled alanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…At the next step of verification, we compared FMAP 2.0 predictions of TM and non-TM peptide arrangements in lipid bilayers with published experimental data. The test set 6 included synthetic pH-triggered membrane peptides with ionizable residues within hydrophobic α-helices studied by solid-state NMR, ATR-FTIR spectroscopy, and OCD , at different pH values (50 data points for 32 peptides). These peptides were designed to examine the pH-dependent equilibrium between membrane-spanning TM α-helices and surface-bound non-TM states in model PC bilayers .…”
Section: Resultsmentioning
confidence: 99%
“…At the next step of verification, we compared FMAP 2.0 predictions of TM and non-TM peptide arrangements in lipid bilayers with published experimental data. The test set 6 included synthetic pH-triggered membrane peptides with ionizable residues within hydrophobic α-helices studied by solid-state NMR, ATR-FTIR spectroscopy, and OCD , at different pH values (50 data points for 32 peptides). These peptides were designed to examine the pH-dependent equilibrium between membrane-spanning TM α-helices and surface-bound non-TM states in model PC bilayers .…”
Section: Resultsmentioning
confidence: 99%
“…Because gel-phase conditions were not investigated, the lipid phase is not a factor for the Glu titrations reported here. Acyl chain unsaturation also is unlikely to be a significant factor for the titration behavior, as related experiments have shown that chain unsaturation is relatively unimportant for the lipid interactions or orientations of helices with charged residues . By contrast, bilayer thickness is highly important for regulating the orientations of Arg-containing helices …”
Section: Discussionmentioning
confidence: 99%
“…Acyl chain unsaturation also is unlikely to be a significant factor for the titration behavior, as related experiments have shown that chain unsaturation is relatively unimportant for the lipid interactions or orientations of helices with charged residues. 26 By contrast, bilayer thickness is highly important for regulating the orientations of Arg-containing helices. 26 The results for titrating glutamic acid E4 reveal a pK a (4.8) close to the aqueous value at the DLPC membrane interface (Figure 4) and higher values of 6.3 and 11, respectively, in DMPC and DOPC.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These features will be important for understanding the plasticity of protein functional domains for which, notably, the cholesterol content also is a significant regulatory factor. 23,34,35 While induced by E16, the disorder in the R 14 E 16 GWALP23 population can be attributed to both residues E16 and R14 and their possible interactions and influence upon the core helix orientations and terminal fraying. When E16 is present without R14, the 2 H resonances are broad 20 yet the number of states remains few.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Partial unwinding of the helix terminals is anticipated, even for the parent R14 helix, with the extent of fraying notably depending on the identities and ionization states of particular residues near the membrane interface. , While small changes in the local fraying are detected easily by the highly sensitive 2 H NMR methods, such changes involving helix terminal disorder may not necessarily be reflected in the circular dichroism spectra. , Notably, the helix disorder, whether arising from changes in end fraying or orientations of the core helix, is lipid-dependent as well as pH-dependent as the detailed behavior varies among bilayers of DLPC, DMPC, and DOPC. These features will be important for understanding the plasticity of protein functional domains for which, notably, the cholesterol content also is a significant regulatory factor. ,, …”
Section: Discussionmentioning
confidence: 99%